Consensus and divergence in the social representations of political leadership - Torres Stöckl, Cynthia María (Pontificia Universidad Católica del Perú, 2014)
The aim of this paper is to analyze descriptively the consensual and differential dimensions of political leadership social representations, based on a convenience sample composed of Psychology, Philosophy and Humanities college students from Tucumán National University, Argentina. Results show a representational universe in tension characterized by opposite nuclear components: Leadership and Representation versus Power and Corruption, as well as opposite dimensions: Features / Positive Political Aspects versus Features / Negative Political Aspects, as well as two relevant clusters consistent with the latter two. Differences are also observed when analyzing variables such as: year in college, student’s political group membership, university political involvement and background / types of political figures.